A double conductive network structure basalt fiber electromagnetic shielding paper and its preparation method

The ANF-enhanced double-conductive network structure BF electromagnetic shielding paper solves the problems of easy corrosion and difficult interface bonding of traditional electromagnetic shielding materials in extreme environments, achieves high-efficiency electromagnetic shielding and environmental stability, and avoids the hazards of metal palladium catalysts.

CN118910919BActive Publication Date: 2025-09-12SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411015310.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-09-12
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

Traditional electromagnetic shielding materials are prone to corrosion and aging in extreme environments, and the chemical plating process using metal palladium as a catalyst has potential hazards to the environment and human health. In addition, BF fibers are difficult to bond to the interface of paper-based materials.

Method used

ANF ​​is used as the reinforcing phase, and a BF electromagnetic shielding paper with a double conductive network structure is constructed through acid etching, coupling agent modification and chemical copper-nickel plating treatment. ANF and BF are used to form a composite structure similar to reinforced concrete, which improves the interfacial bonding strength and avoids the use of metal palladium catalysts.

Benefits of technology

It achieves high electrical conductivity and high electromagnetic interference shielding effectiveness in extreme environments, has excellent electromagnetic shielding performance and Joule heating performance, and exhibits a high shielding effectiveness to thickness ratio of 800 to 2000dB mm-1 at a thickness of 0.02 to 0.2mm, significantly improving environmental stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004965517780000011
    Figure HDA0004965517780000011
  • Figure HDA0004965517780000012
    Figure HDA0004965517780000012
  • Figure HDA0004965517780000021
    Figure HDA0004965517780000021
Patent Text Reader

Abstract

The present invention provides a basalt electromagnetic shielding paper with a dual-conductive network structure and a preparation method thereof. The preparation method comprises: modifying and chemically copper-plating basalt fibers; preparing an aramid nanofiber dispersion; mixing with the copper-plated basalt fibers and subjecting the dispersion to vacuum-assisted filtration to prepare a composite paper; and chemically nickel-plating the composite paper to prepare the basalt electromagnetic shielding paper with a dual-conductive network structure. Due to the dual-conductive network structure, the basalt electromagnetic shielding paper not only has a high electromagnetic shielding efficiency of 40 to 90 dB, but also exhibits an electromagnetic shielding efficiency of 800 to 2000 dB at a thickness of 0.02 to 0.2 mm. ‑1 The double-conductive network structure basalt electromagnetic shielding paper also has excellent Joule heating performance and exhibits stable and long-lasting electromagnetic shielding performance in extreme environments (such as acid and alkaline solutions, ignition, high and low temperature environments, ultrasonic cleaning, and long-term storage).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the intersecting field of electromagnetic shielding materials and papermaking technology, and in particular to a basalt fiber electromagnetic shielding paper with a double conductive network structure and a preparation method thereof. Background Art

[0002] Chemical plating technology has the advantages of uniform coating, wide applicability and relatively low cost. However, the traditional chemical plating process using metal palladium as a catalyst has some potential hazards to the environment and human health. Therefore, it is crucial to find and develop an environmentally friendly and sustainable chemical plating method. At the same time, traditional electromagnetic shielding materials have disadvantages such as corrosion and aging in extreme environments. Traditional electromagnetic shielding materials have the problems of heavy weight and high rigidity, which may be limited in extreme environment applications with strict requirements on weight and flexibility. Therefore, finding new electromagnetic shielding materials with resistance to extreme environments has become an important direction of current research to meet the special needs of aerospace, military, energy and other fields for electromagnetic shielding in extreme environments.

[0003] Lightweight, high-performance, and versatile applications of electromagnetic shielding materials have become a significant development trend. Paper-based materials possess a unique three-dimensional network structure with adjustable composition, structure, and thickness. As effective and practical materials for EMI (electromagnetic interference) shielding applications, they have attracted significant attention, particularly in portable devices, flexible protective materials, and aerospace.

[0004] Basalt fiber (BF) is an emerging high-performance inorganic fiber known for its environmental friendliness and pollution-free properties, earning it the title of "21st-century green industrial material." The fiber exhibits high modulus, high strength, electrical insulation, excellent chemical stability, good heat resistance (-265°C-800°C), low thermal conductivity, and low moisture absorption. Currently, BF is primarily used in wastewater treatment, sound absorption, and wear-resistant materials, and continues to attract significant attention. To date, there have been no reports on its application in electromagnetic shielding materials for extreme environments, and due to BF's smooth surface and chemical inertness, interfacial bonding in paper applications presents numerous challenges. Summary of the Invention

[0005] The purpose of the present invention is to provide a double conductive network structure BF electromagnetic shielding paper and a preparation method thereof, using ANF (aramid nanofiber) as a reinforcing phase to improve the interface bonding problem of BF in paper-based materials.

[0006] To achieve the above purpose, the technical solution of the present invention is as follows:

[0007] A method for preparing a double conductive network structure BF electromagnetic shielding paper comprises the following steps:

[0008] (1) Acid etching of fiber surface: Prepare piranha solution to acid etch BF;

[0009] (2) Coupling agent modification: the BF after acid etching in (1) is modified with an amino silane coupling agent;

[0010] (3) Activation: The modified BF from (2) is placed in an activation solution for activation treatment and cleaning, and then placed in a reducing agent solution for reduction treatment and cleaning;

[0011] (4) Plating: placing the BF obtained in (3) in a chemical plating solution for chemical copper plating to obtain a copper-plated basalt fiber mixed solution;

[0012] (5) mixing the copper-plated BF mixed solution obtained in (4) with the ANF dispersion, and preparing a composite paper by a vacuum-assisted filtration method;

[0013] (6) activating and cleaning the composite paper prepared in (5), and then placing it in a reducing agent solution for reduction and cleaning;

[0014] (7) placing the composite paper obtained in (6) in a chemical plating solution for chemical nickel plating;

[0015] (8) Drying the nickel-plated composite paper in (7) to obtain a double conductive network electromagnetic shielding paper.

[0016] Furthermore, the piranha solution in (1) is a mixture of H2SO4 (sulfuric acid) and H2O2 (hydrogen peroxide) with a volume ratio of 1:1 to 3:1, an acid etching time of 0.5 to 2 hours, and an acid etching temperature of 70 to 100°C;

[0017] Furthermore, the (2) is specifically as follows: first, hydrolyzing an amino silane coupling agent with a mixed solution of ethanol and deionized water in a mass ratio of 1:1 to 10:1 to obtain an amino silane coupling agent solution with a concentration of 1 to 5 wt%, wherein the amino silane coupling agent includes at least one of KH550, KH792, and KH602; then adding BF after acid etching for modification, wherein the concentration of BF after acid etching is 0.5 to 6 g / L, the modification temperature is 40 to 80° C., and the modification time is 8 to 24 h;

[0018] Furthermore, the composition of the chemical copper plating solution in (4) is 10-60 g / L EDTA-2Na (disodium ethylenediaminetetraacetic acid), 10-50 g / L NaKC4H4O6 (sodium potassium tartrate), 5-25 g / L CuSO4·5H2O (copper sulfate pentahydrate), 0.01-0.2 g / L K4Fe(CN)6 (potassium ferrocyanide), 10-60 ml / L CH2O (formaldehyde), 0.01-0.5 g / L 10H8N2 (2-methyl-6-nitroquinoline);

[0019] Furthermore, the plating temperature is 40-80° C., the pH value of the copper plating solution is 10-12, and the plating time is 20-80 min.

[0020] Furthermore, the copper plating BF content in the obtained mixed solution is 50 to 90 wt%;

[0021] Furthermore, it is characterized in that the preparation method of the ANF dispersion in (5) is specifically as follows: aramid fiber, KOH (potassium hydroxide), C2H6OS (dimethyl sulfoxide) and deionized water are mixed and stirred to crack the aramid fiber to form ANF, and then deionized water is added to perform a protonation reduction reaction, and after repeated washing, an ANF dispersion is obtained;

[0022] Furthermore, the activation solution in (3) and (6) comprises AgNO3 (silver nitrate) and deionized water, i.e., silver nitrate solution;

[0023] Furthermore, the reducing agent in (3) and (6) includes NaBH4 (sodium borohydride) and deionized water, i.e., sodium borohydride solution;

[0024] Furthermore, the steps (3) and (6) are as follows: immersing the modified BF in a 5-20 g / L AgNO3 (silver nitrate) solution for 5-60 min, and then rinsing with deionized water;

[0025] Further, the substrate is immersed in a NaBH4 solution having a concentration of 20 to 50 g / L and reacted for 10 to 30 minutes, and then rinsed with deionized water again;

[0026] Furthermore, the nickel plating solution in (7) is composed of 10-40 g / L C6H5Na3O7·2H2O (sodium molybdate), 10-40 g / L NiSO4·6H2O (nickel sulfate hexahydrate), 5-20 g / L NaH2PO2·H2O (sodium hypophosphite), 1-5 g / L DMAB (dimethylamine borane), and 0.01-0.1 g / L SDS (sodium dodecyl sulfate);

[0027] Furthermore, the plating temperature is 30-80° C., the pH value of the nickel plating solution is 9-12, and the plating time is 10-100 minutes.

[0028] A double conductive network structure BF electromagnetic shielding paper, the thickness of the double conductive network electromagnetic shielding paper is 0.02-0.2mm;

[0029] Furthermore, the double conductive network electromagnetic shielding paper has a total electromagnetic shielding effectiveness of 10 to 90 dB at a frequency of 8.2 to 12.4 GHz.

[0030] A double conductive network structure BF electromagnetic shielding paper is used as a smart film, personal thermal management or wearable electromagnetic protection field.

[0031] The above technical solution has the following advantages or beneficial effects:

[0032] The present invention provides a double-conductive network structure BF electromagnetic shielding paper and a preparation method thereof. BF has the characteristics of high modulus, high strength, excellent chemical stability, good heat resistance, etc. However, BF has a smooth surface and is chemically inert, making it difficult to form surface bonding with other materials. The present invention adopts ANF as a reinforcing phase to improve the interface bonding problem of BF in paper-based materials.

[0033] Furthermore, the present invention uses the prepared piranha solution to perform acid etching on BF to make it rich in silanol groups.

[0034] Furthermore, a coupling agent surface modification technology is used to modify the etched BF using a silane coupling agent, so that the BF can directly adsorb silver ions. This not only avoids the environmental pollution caused by the use of stannous chloride for sensitization treatment in the existing technology, but also reduces the number of operating steps.

[0035] Furthermore, BF absorbs AgNO3 solution, and the silver ions form coordination with amino groups and are reduced to silver nanoparticles, which serve as catalytic centers for subsequent chemical plating, thus avoiding the potential harm to the environment and human health caused by using metal palladium as a catalyst in the traditional chemical plating process; thereafter, chemical copper plating treatment is carried out to prepare copper-plated BF.

[0036] Furthermore, ANF was prepared through a KOH system, and a copper-plated BF / ANF composite paper with a reinforced concrete layered structure was prepared using a vacuum-assisted filtration method. Subsequently, chemical nickel plating was performed through silver ion activation to form a double conductive network structure inside and on the surface of the composite paper. The copper-plated BF served as the skeleton of the electromagnetic shielding paper and was interspersed between the ANF to form a "reinforced concrete" structure, which improved the environmental stability of the composite paper under extreme conditions. By chemically copper-plating the BF and chemically nickel-plating the surface of the composite paper, a double conductive network structure was constructed inside and on the surface of the composite paper. Due to the synergistic effect of the double conductive network structure, the electromagnetic shielding effectiveness of the composite paper was significantly improved, that is, the composite paper not only had a shielding efficiency of 100 to 500 S cm -1 It has high electrical conductivity and high electromagnetic interference shielding effectiveness (EMI SE) of 40-90dB, and shows 800-2000dB mm at a thickness of 0.02-0.2mm. -1 High shielding effectiveness to thickness ratio (SE / t).

[0037] Furthermore, the composite paper consumes electromagnetic waves through electrical loss, magnetic loss and multiple reflection loss. Due to the excellent chemical stability of the nickel layer, it is wrapped on the surface of the composite paper, preventing the corrosion of the internal copper-plated fibers, and effectively improving the extreme environmental stability of the composite paper. At the same time, thanks to the establishment of a double conductive network structure, the composite paper not only exhibits excellent electromagnetic shielding performance, but also has excellent Joule heating performance, and exhibits stable and long-lasting electromagnetic shielding performance in extreme environments (such as acid and alkaline solutions, ignition, high and low temperature environments, ultrasonic cleaning, and long-term storage). BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The following are SEM (field emission scanning electron microscope) images of copper-plated BF; (a) is the surface SEM image of copper-plated BF; (b) is the cross-sectional SEM image of copper-plated BF; (c) is the magnified cross-sectional SEM image of copper-plated BF;

[0039] Figure 2 Surface and cross-sectional SEM images of 80 wt% copper-plated BF / ANF composite paper and nickel-plated composite paper; (a) is a surface SEM image of 80 wt% copper-plated BF / ANF composite paper; (b) is a cross-sectional SEM image of 80 wt% copper-plated BF / ANF composite paper; (c) is a surface SEM image of nickel-plated composite paper; (d) is a cross-sectional SEM image of nickel-plated composite paper;

[0040] Figure 3 The electromagnetic shielding effectiveness curve of 80wt% copper-plated BF / ANF composite paper;

[0041] Figure 4 The shielding effectiveness curve of composite paper treated with different nickel plating times is shown in FIG.

[0042] Figure 5 The graph shows the change in electromagnetic shielding effectiveness of composite paper with nickel plating only and composite paper with double conductive network structure;

[0043] Figure 6 Schematic diagram of the change of electromagnetic shielding effectiveness of the double conductive network structure electromagnetic shielding paper under extreme environment; (a) shows the change of electromagnetic shielding effectiveness of the composite paper after being immersed in acid and alkali solution for a period of time; (b) shows the change of electromagnetic shielding effectiveness of the composite paper after being immersed in liquid nitrogen solution for a period of time; (c) shows the change of electromagnetic shielding effectiveness of the composite paper after high-temperature annealing treatment; (d) shows the change of electromagnetic shielding effectiveness of the composite paper after being ignited by an alcohol lamp; (e) shows the change of electromagnetic shielding effectiveness of the composite paper after ultrasonic treatment; (f) shows the change of electromagnetic shielding effectiveness of the composite paper after being placed for a period of time;

[0044] Figure 7 This is the relationship between temperature and time when a gradient voltage is applied to the double conductive network structure composite paper;

[0045] Figure 8 This is the tensile stress-strain diagram of the double conductive network structure composite paper after nickel plating for 20 minutes. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts should fall within the scope of protection of the present invention.

[0047] A double conductive network electromagnetic shielding paper and a preparation method thereof, comprising the following specific steps:

[0048] (1) Acid etching of fiber surface: Prepare piranha solution for acid etching of BF. The piranha solution is a mixture of H2SO4 and H2O2 with a volume ratio of 1:1 to 3:1. The acid etching time is 0.5 to 2 h and the acid etching temperature is 70 to 100 °C.

[0049] (2) Coupling agent modification: first, hydrolyze the aminosilane coupling agent with a mixed solution of ethanol and deionized water in a mass ratio of 1:1 to 10:1 to obtain an aminosilane coupling agent solution with a concentration of 1 to 5 wt%, wherein the aminosilane coupling agent includes at least one of KH550, KH792, and KH602; then add the acid-etched BF for modification, wherein the concentration of the acid-etched BF is 0.5 to 6 g / L, the modification temperature is 40 to 80°C, and the modification time is 8 to 24 h;

[0050] (3) Activation: The BF modified in (2) is immersed in a 5-20 g / L AgNO3 (silver nitrate) solution for activation treatment, reacting for 5-60 min, and then rinsed with deionized water; then immersed in a 20-50 g / L NaBH4 solution for reduction treatment, reacting for 10-30 min, and then rinsed with deionized water again;

[0051] (4) Plating: The BF obtained in (3) is placed in a chemical plating solution for chemical copper plating. The composition of the chemical copper plating solution is 10-60 g / L EDTA-2Na, 10-50 g / L NaKC4H4O6, 5-25 g / L CuSO4·5H2O, 0.01-0.2 g / L K4Fe(CN)6, 10-60 ml / L CH2O, 0.01-0.5 g / L 10H8N2, plating temperature of 40-80°C, pH of copper plating solution of 10-12, plating time of 20-80min, to obtain copper plating BF mixed solution;

[0052] (5) mixing the copper-plated BF mixed solution obtained in (4) with the ANF dispersion, and preparing a composite paper by a vacuum-assisted filtration method;

[0053] (6) immersing the composite paper prepared in (5) in a 5-20 g / L AgNO3 solution for activation treatment, reacting for 5-60 min, and then rinsing with deionized water; then immersing in a 20-50 g / L NaBH4 solution for reduction treatment, reacting for 10-30 min, and then rinsing with deionized water again;

[0054] (7) Plating the composite paper obtained in (6) in a chemical plating solution for chemical nickel plating, wherein the composition of the nickel plating solution is 10-40 g / L C6H5Na3O7·2H2O, 10-40 g / L NiSO4·6H2O, 5-20 g / L NaH2PO2·H2O, 1-5 g / L DMAB, and 0.01-0.1 g / L SDS, the plating temperature is 30-80°C, the pH value of the nickel plating solution is 9-12, and the plating time is 10-100 min;

[0055] (8) The nickel-plated composite paper in (7) is dried at a temperature of 80 to 120° C. for 8 to 80 minutes to obtain a double conductive network electromagnetic shielding paper.

[0056] Preferably, the copper-plated BF content in the mixed solution obtained in (4) is 50-90 wt%;

[0057] Preferably, the preparation method of the ANF dispersion in (5) is as follows: aramid fiber, KOH, C2H6OS and deionized water are mixed and stirred to crack the aramid fiber to form ANF, and then deionized water is added to carry out protonation reduction reaction, and after repeated washing, the ANF dispersion is obtained.

[0058] A double conductive network structure BF electromagnetic shielding paper, the thickness of the double conductive network electromagnetic shielding paper is 0.02-0.2mm;

[0059] Preferably, the double conductive network electromagnetic shielding paper has a total electromagnetic shielding effectiveness of 10 to 90 dB at a frequency of 8.2 to 12.4 GHz.

[0060] A double conductive network structure BF electromagnetic shielding paper is used as a smart film, personal thermal management or wearable electromagnetic protection field.

[0061] The present invention will be further described in detail below with reference to specific embodiments, which are intended to explain the present invention rather than to limit it.

[0062] Example 1:

[0063] The method for preparing the electromagnetic shielding paper with a double conductive network structure in this embodiment specifically comprises the following steps:

[0064] (1) preparing a piranha solution to acid-etch BF, wherein the piranha solution is H2SO4 and H2O2 in a volume ratio of 7:3, the acid etching time is 1 h, and the acid etching temperature is 90°C;

[0065] (2) C2H5OH and deionized water were mixed in a certain ratio (C2H5OH: deionized water (mass ratio) = 9:1), and the mixed solution was used to hydrolyze KH-550 to obtain a KH-550 solution with a concentration of 1%; then, BF after acid etching was added thereto for modification, the concentration of BF after acid etching was 6 g / L, the modification temperature was 60°C, and the modification time was 12 h;

[0066] (3) The modified basalt was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0067] (4) The chemical copper plating solution (500 mL) was heated to 60 ° C and the pH of the solution was adjusted with 8M NaOH. When the pH reached 10, CH2O was added and stirred thoroughly. Then, NaOH was added dropwise to raise the pH to 12. The activated BF in (3) was placed in the copper plating solution and reacted for 60 min. The composition of the copper plating solution was 40 g / L EDTA-2Na, 30 g / L NaKC4H4O6, 16 g / L CuSO4·5H2O, 0.05 g / L K4Fe(CN)6, 40 ml / L CH2O, 0.01 g / L 10 H8N2;

[0068] (5) 1 g of aramid fiber, 1.5 g of KOH, 20 ml of deionized water, and 500 ml of C2H6OS were mixed and magnetically stirred at room temperature for 4 h to obtain a dark red ANF solution with a concentration of 0.2%. Then, 41 ml of the ANF solution was measured and deionized water was injected into it under magnetic stirring. The mass ratio of ANF solution to deionized water was 1:2. After repeated washing, an ANF dispersion was obtained.

[0069] The copper-plated BF mixed solution obtained in (4) and the ANF dispersion solution in (5) were mixed, wherein the copper-plated BF content was 80 wt%, and composite paper was prepared by vacuum-assisted filtration;

[0070] (6) The composite paper prepared in (5) was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0071] (7) The composite paper prepared in (6) was then immersed in a plating solution (500 mL) to start a chemical nickel plating reaction; the specific nickel plating solution composition was 34 g / L C6H5Na3O7·2H2O, 27 g / L NiSO4·6H2O, 15 g / L NaH2PO2·H2O, 3 g / L DMAB, and 0.01 g / L SDS. The pH of the nickel plating solution was adjusted to 10 by NH3·H2O (ammonia water), the plating solution temperature was maintained at 50°C, and the reaction was carried out for 20 min;

[0072] (8) The nickel-plated composite paper obtained in (7) was dried at 105° C. for 10 min using a paper sample dryer to obtain a double conductive network electromagnetic shielding paper with a nickel plating time of 20 min.

[0073] like Figure 1 The figure shows the SEM image of copper-plated BF. After chemical copper plating, the surface of BF is covered with dense copper particles, forming a dense and smooth coating. The copper layer is tightly bonded to the fiber, and the thickness of the coating is about 720nm.

[0074] like Figure 8 As shown, it is the tensile stress-strain diagram of the double conductive network structure composite paper after nickel plating for 20 minutes. The composite paper has good mechanical strength.

[0075] Example 2:

[0076] The method for preparing the electromagnetic shielding paper with a double conductive network structure in this embodiment specifically comprises the following steps:

[0077] (1) preparing a piranha solution to acid-etch BF, wherein the piranha solution is H2SO4 and H2O2 in a volume ratio of 7:3, the acid etching time is 1 h, and the acid etching temperature is 90°C;

[0078] (2) C2H5OH and deionized water were mixed in a certain ratio (C2H5OH: deionized water (mass ratio) = 9:1), and the mixed solution was used to hydrolyze KH-550 to obtain a KH-550 solution with a concentration of 1%; then, BF after acid etching was added thereto for modification, the concentration of BF after acid etching was 1 g / L, the modification temperature was 60°C, and the modification time was 12 h;

[0079] (3) The modified basalt was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0080] (4) Heat the chemical copper plating solution to 60°C and use 8M NaOH to adjust the solution pH. When the pH reaches 10, add CH2O and stir thoroughly. Then continue to add NaOH dropwise to raise the pH to 12. Place the activated BF in (3) into the copper plating solution and react for 60 minutes. The copper plating solution composition is 40g / L LEDTA-2Na, 30g / L NaKC4H4O6, 16g / L CuSO4·5H2O, 0.05g / L K4Fe(CN)6, 40ml / L CH2O, 0.01g / LC 10 H8N2;

[0081] (5) 1 g of aramid fiber, 1.5 g of KOH, 20 ml of deionized water, and 500 ml of C2H6OS were mixed and magnetically stirred at room temperature for 4 h to obtain a deep red ANF solution with a concentration of 0.2%. Then, 41 ml of the ANF solution was measured and deionized water was injected into it under magnetic stirring. The mass ratio of the aramid nanofiber solution to deionized water was 1:2. After repeated washing, an ANF dispersion was obtained.

[0082] The copper-plated BF mixed solution obtained in (4) and the ANF dispersion solution in (5) were mixed, wherein the copper-plated BF content was 80 wt%, and composite paper was prepared by vacuum-assisted filtration;

[0083] (6) The composite paper prepared in (5) was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0084] (7) The composite paper prepared in (6) was then immersed in a plating solution (500 mL) to start a chemical nickel plating reaction; the specific nickel plating solution composition was 34 g / L C6H5Na3O7·2H2O, 27 g / L NiSO4·6H2O, 15 g / LNaH2PO2·H2O, 3 g / L DMAB, and 0.01 g / L SDS. The pH of the nickel plating solution was adjusted to 10 by NH3·H2O, the plating solution temperature was maintained at 50°C, and the reaction was carried out for 40 min;

[0085] (8) The nickel-plated composite paper obtained in (7) was dried at 105° C. for 10 min using a paper sample dryer to obtain a double conductive network electromagnetic shielding paper with a nickel plating time of 40 min.

[0086] Example 3:

[0087] The method for preparing the electromagnetic shielding paper with a double conductive network structure in this embodiment specifically comprises the following steps:

[0088] (1) preparing a piranha solution to acid-etch BF, wherein the piranha solution is H2SO4 and H2O2 in a volume ratio of 7:3, the acid etching time is 1 h, and the acid etching temperature is 90°C;

[0089] (2) C2H5OH and deionized water were mixed in a certain ratio (C2H5OH: deionized water (mass ratio) = 9:1), and the mixed solution was used to hydrolyze KH-550 to obtain a KH-550 solution with a concentration of 1%; then, BF after acid etching was added thereto for modification, the concentration of BF after acid etching was 0.5 g / L, the modification temperature was 60°C, and the modification time was 12 h;

[0090] (3) The modified basalt was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0091] (4) Heat the chemical copper plating solution (500 mL) to 60°C and adjust the solution pH with 8M NaOH. When the pH reaches 10, add CH2O and stir thoroughly. Then continue to add NaOH dropwise to raise the pH to 12. Place the activated BF in (3) into the copper plating solution and react for 60 minutes. The copper plating solution composition is 40 g / L EDTA-2Na, 30 g / L NaKC4H4O6, 16 g / L CuSO4·5H2O, 0.05 g / L K4Fe(CN)6, 40 ml / L CH2O, 0.01 g / LC 10 H8N2;

[0092] (5) 1 g of aramid fiber, 1.5 g of KOH, 20 ml of deionized water, and 500 ml of C2H6OS were mixed and magnetically stirred at room temperature for 4 h to obtain a dark red ANF solution with a concentration of 0.2%. Then, 41 ml of the ANF solution was measured and deionized water was injected into it under magnetic stirring. The mass ratio of ANF solution to deionized water was 1:2. After repeated washing, an ANF dispersion was obtained;

[0093] The copper-plated BF mixed solution obtained in (4) and the ANF dispersion solution in (5) were mixed, wherein the copper-plated BF content was 80 wt%, and composite paper was prepared by vacuum-assisted filtration;

[0094] (6) The composite paper prepared in (5) was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0095] (7) The composite paper prepared in (6) was then immersed in a plating solution (500 mL) to start a chemical nickel plating reaction; the specific nickel plating solution composition was 34 g / L C6H5Na3O7·2H2O, 27 g / L NiSO4·6H2O, 15 g / L NaH2PO2·H2O, 3 g / L DMAB, and 0.01 g / L SDS. The pH of the nickel plating solution was adjusted to 10 by NH3·H2O, the plating solution temperature was maintained at 50°C, and the reaction was carried out for 60 min;

[0096] (8) The nickel-plated composite paper obtained in (7) was dried at 105° C. for 10 min using a paper sample dryer to obtain a double conductive network electromagnetic shielding paper with a nickel plating time of 60 min.

[0097] Example 4:

[0098] The method for preparing the electromagnetic shielding paper with a double conductive network structure in this embodiment specifically comprises the following steps:

[0099] (1) preparing a piranha solution to acid-etch BF, wherein the piranha solution is H2SO4 and H2O2 in a volume ratio of 7:3, the acid etching time is 1 h, and the acid etching temperature is 90°C;

[0100] (2) C2H5OH and deionized water were mixed in a certain ratio (C2H5OH: deionized water (mass ratio) = 9:1), and the mixed solution was used to hydrolyze KH-550 to obtain a KH-550 solution with a concentration of 1%; then, BF after acid etching was added thereto for modification, the concentration of BF after acid etching was 3 g / L, the modification temperature was 60°C, and the modification time was 12 h;

[0101] (3) The modified basalt was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0102] (4) Heat the chemical copper plating solution (500 mL) to 60°C and adjust the solution pH with 8M NaOH. When the pH reaches 10, add CH2O and stir thoroughly. Then continue to add NaOH dropwise to raise the pH to 12. Place the activated BF in (3) into the copper plating solution and react for 60 minutes. The copper plating solution composition is 40 g / L EDTA-2Na, 30 g / L NaKC4H4O6, 16 g / L CuSO4·5H2O, 0.05 g / L K4Fe(CN)6, 40 ml / L CH2O, 0.01 g / LC 10 H8N2;

[0103] (5) 1 g of aramid fiber, 1.5 g of KOH, 20 ml of deionized water, and 500 ml of C2H6OS were mixed and magnetically stirred at room temperature for 4 h to obtain a dark red ANF solution with a concentration of 0.2%. Then, 41 ml of the ANF solution was measured and deionized water was injected into it under magnetic stirring. The mass ratio of ANF to deionized water was 1:2. After repeated washing, an ANF dispersion was obtained.

[0104] The copper-plated BF mixed solution obtained in (4) and the ANF dispersion solution in (5) were mixed, wherein the copper-plated BF content was 80 wt%, and composite paper was prepared by vacuum-assisted filtration;

[0105] (6) The composite paper prepared in (5) was immersed in a AgNO3 solution (concentration of 10 g / L) for 30 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 40 g / L) for 15 min, and then rinsed with deionized water again;

[0106] (7) The composite paper prepared in (6) was then immersed in a plating solution (500 mL) to start a chemical nickel plating reaction; the specific nickel plating solution composition was 34 g / L C6H5Na3O7·2H2O, 27 g / L NiSO4·6H2O, 15 g / LNaH2PO2·H2O, 3 g / L DMAB, and 0.01 g / L SDS. The pH of the nickel plating solution was adjusted to 10 by NH3·H2O, the plating solution temperature was maintained at 50°C, and the reaction was carried out for 80 min;

[0107] (8) The nickel-plated composite paper obtained in (7) was dried at 105° C. for 10 min using a paper sample dryer to obtain a double conductive network electromagnetic shielding paper with a nickel plating time of 80 min.

[0108] like Figure 2Figure 2 shows the surface and cross-sectional SEM images of 80 wt% copper-plated BF / ANF composite paper and nickel-plated composite paper. The copper-plated BF acts as the skeleton of the composite paper and is interwoven inside to form a conductive network, while the ANF, as a reinforcing phase, is filled between the copper-plated BF to form a structure similar to "reinforced concrete."

[0109] Preferably, during the vacuum-assisted filtration process, a unique layered structure is formed, which extends the propagation path of the electromagnetic waves, thereby increasing the barrier effect on the electromagnetic waves;

[0110] Preferably, after the composite paper is nickel-plated, a dense nickel layer is formed on its surface, constructing a complete conductive network;

[0111] Preferably, this conductive network and the copper-plated BF inside the composite paper form a double conductive network structure, which effectively improves the loss of electromagnetic waves, thereby improving the electromagnetic shielding effectiveness of the composite paper. At the same time, the dense nickel layer has the characteristics of corrosion resistance and high temperature resistance, and is wrapped around the surface of the composite paper, effectively protecting the internal network structure and significantly improving the stability of the composite paper in extreme environments.

[0112] like Figure 3 As shown, it is the electromagnetic shielding effectiveness curve of 80wt% copper-plated BF / ANF composite paper. In the X-band, its average electromagnetic shielding effectiveness is 18.96dB.

[0113] like Figure 4 As shown in the figure, the shielding effectiveness curve of the composite paper treated with different nickel plating times is shown. As the nickel plating time increases, the electromagnetic shielding effectiveness of the composite paper gradually increases, from 40.7dB at 20min to 74dB at 80min.

[0114] like Figure 6 The figure shows the change of electromagnetic shielding effectiveness of the double conductive network structure electromagnetic shielding paper under extreme environment;

[0115] Preferably, (a) shows the change in electromagnetic shielding effectiveness of electromagnetic shielding paper after being immersed in strong acid and alkali solutions for 24 hours. Due to the effective protection provided by the external nickel layer, the electromagnetic shielding effectiveness of the sample did not change significantly, showing excellent corrosion resistance;

[0116] Preferably, (b-d) show the changes in electromagnetic shielding of the composite paper after being immersed in liquid nitrogen for 7 hours, placed in a 300°C tube furnace for 10 hours, and ignited under an alcohol lamp for 60 seconds;

[0117] Preferably, the results show that after these treatments, the electromagnetic shielding effectiveness of the samples remains above 80%;

[0118] Preferably, under the action of high-frequency mechanics, the electromagnetic shielding paper still shows a relatively satisfactory effect;

[0119] Preferably, (e) shows that after ultrasonic cleaning for 1 hour, the electromagnetic shielding effectiveness of the sample slightly decreases from 74dB to 68.04dB, with a retention rate of about 91%;

[0120] Preferably, (f) shows that after being stored at room temperature for 6 months, the electromagnetic shielding effectiveness of the composite paper still remains at 98%;

[0121] Preferably, these results illustrate that the double conductive network structure electromagnetic shielding paper has excellent electromagnetic shielding stability in extreme environments, mainly due to its double conductive network structure design and the superior performance of the nickel layer and nickel-plated BF, which makes the composite material exhibit significant environmental stability.

[0122] like Figure 7 As shown, this is a temperature-time relationship diagram of the double conductive network structure composite paper when a gradient voltage is applied. The composite paper has a rapid temperature response under different voltages, indicating that the composite paper has good temperature controllability.

[0123] Example 5:

[0124] The method for preparing the electromagnetic shielding paper with a double conductive network structure in this embodiment specifically comprises the following steps:

[0125] (1) preparing a piranha solution to acid-etch BF, wherein the piranha solution is H2SO4 and H2O2 in a volume ratio of 1:1, the acid etching time is 0.5 h, and the acid etching temperature is 70°C;

[0126] (2) C2H5OH and deionized water were mixed in a certain proportion (C2H5OH: deionized water (mass ratio) = 1:1), and the mixed solution was used to hydrolyze KH-550 to obtain a KH-550 solution with a concentration of 5%; then, BF after acid etching was added thereto for modification, the concentration of BF after acid etching was 4 g / L, the modification temperature was 40°C, and the modification time was 8 h;

[0127] (3) The modified basalt was immersed in a AgNO3 solution (concentration of 5 g / L) for 5 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 20 g / L) for 10 min, and then rinsed with deionized water again;

[0128] (4) Heat the chemical copper plating solution (500 mL) to 40 ° C, and use 8M NaOH to adjust the pH of the solution, add CH2O, stir thoroughly, and then continue to add NaOH dropwise to raise the pH to 10; place the BF activated in (3) into the copper plating solution and react for 20 minutes; the copper plating solution composition is 10g / L LEDTA-2Na, 10g / L NaKC4H4O6, 5g / L CuSO4·5H2O, 0.01g / L K4Fe(CN)6, 10ml / L CH2O, 0.5g / LC 10 H8N2;

[0129] (5) 1 g of aramid fiber, 1.5 g of KOH, 20 ml of deionized water, and 500 ml of C2H6OS were mixed and magnetically stirred at room temperature for 4 h to obtain a dark red ANF solution with a concentration of 0.2%. Then, 41 ml of the ANF solution was measured and deionized water was injected into it under magnetic stirring. The mass ratio of ANF to deionized water was 1:2. After repeated washing, an ANF dispersion was obtained.

[0130] The copper-plated BF mixed solution obtained in (4) and the ANF dispersion solution in (5) were mixed, wherein the copper-plated BF content was 50 wt%, and composite paper was prepared by vacuum-assisted filtration;

[0131] (6) The composite paper prepared in (5) was immersed in a AgNO3 solution (concentration of 5 g / L) for 5 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 20 g / L) for 10 min, and then rinsed with deionized water again;

[0132] (7) The composite paper prepared in (6) was then immersed in a plating solution (500 mL) to start a chemical nickel plating reaction; the specific nickel plating solution composition was 10 g / L C6H5Na3O7·2H2O, 10 g / L NiSO4·6H2O, 5 g / LNaH2PO2·H2O, 1 g / L DMAB, and 0.1 g / L SDS. The pH of the nickel plating solution was adjusted to 9 by NH3·H2O, the plating solution temperature was maintained at 30°C, and the reaction was carried out for 10 min;

[0133] (8) The nickel-plated composite paper obtained in (7) was dried at 80° C. for 8 min using a paper sample dryer to obtain a double conductive network electromagnetic shielding paper with a nickel plating time of 10 min.

[0134] Example 6:

[0135] The method for preparing the electromagnetic shielding paper with a double conductive network structure in this embodiment specifically comprises the following steps:

[0136] (1) preparing a piranha solution to acid-etch BF, wherein the piranha solution is H2SO4 and H2O2 in a volume ratio of 3:1, the acid etching time is 2 h, and the acid etching temperature is 100°C;

[0137] (2) C2H5OH and deionized water were mixed in a certain ratio (C2H5OH: deionized water (mass ratio) = 10:1), and the mixed solution was used to hydrolyze KH-550 to obtain a KH-550 solution with a concentration of 1%; then, BF after acid etching was added thereto for modification, the concentration of BF after acid etching was 1 g / L, the modification temperature was 80°C, and the modification time was 24 h;

[0138] (3) The modified basalt was immersed in a AgNO3 solution (concentration of 20 g / L) for 60 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 50 g / L) for 30 min, and then rinsed with deionized water again;

[0139] (4) Heat the chemical copper plating solution (500 mL) to 80°C and adjust the solution pH with 8M NaOH. When the pH reaches 10, add CH2O and stir thoroughly. Then continue to add NaOH dropwise to raise the pH to 12. Place the activated BF in (3) into the copper plating solution and react for 80 minutes. The copper plating solution composition is 60 g / L EDTA-2Na, 50 g / L NaKC4H4O6, 25 g / L CuSO4·5H2O, 0.2 g / L K4Fe(CN)6, 60 ml / L CH2O, 0.01 g / LC 10 H8N2;

[0140] (5) 1 g of aramid fiber, 1.5 g of KOH, 20 ml of deionized water, and 500 ml of C2H6OS were mixed and magnetically stirred at room temperature for 4 h to obtain a dark red ANF solution with a concentration of 0.2%. Then, 41 ml of the ANF solution was measured and deionized water was injected into it under magnetic stirring. The mass ratio of ANF to deionized water was 1:2. After repeated washing, an ANF dispersion was obtained.

[0141] The copper-plated BF mixed solution obtained in (4) and the ANF dispersion solution in (5) were mixed, wherein the copper-plated BF content was 90 wt%, and composite paper was prepared by vacuum-assisted filtration;

[0142] (6) The composite paper prepared in (5) was immersed in a AgNO3 solution (concentration of 20 g / L) for 60 min, then rinsed with deionized water, and then immersed in a NaBH4 solution (concentration of 50 g / L) for 30 min, and then rinsed with deionized water again;

[0143] (7) The composite paper prepared in (6) was then immersed in a plating solution (500 mL) to start a chemical nickel plating reaction; the specific nickel plating solution composition was 40 g / L C6H5Na3O7·2H2O, 40 g / L NiSO4·6H2O, 20 g / LNaH2PO2·H2O, 5 g / L DMAB, and 0.01 g / L SDS. The pH of the nickel plating solution was adjusted to 12 by NH3·H2O, the plating solution temperature was maintained at 80°C, and the reaction was carried out for 100 min.

[0144] (8) The nickel-plated composite paper obtained in (7) was dried at 120° C. for 80 min using a paper sample dryer to obtain a double conductive network electromagnetic shielding paper with a nickel plating time of 100 min.

[0145] Comparative Example 1:

[0146] In this comparative example, the only difference from Example 4 is that no copper-plated BF is added, and the composite paper is prepared only from ANF and then subjected to chemical nickel plating for 80 minutes.

[0147] like Figure 5 The figure shows the changes in the electromagnetic shielding effectiveness of the composite paper with only nickel plating and the composite paper with a double conductive network structure. Compared with the nickel-plated composite paper without the addition of copper-plated BF, the composite paper with a double conductive network structure shows more excellent electromagnetic shielding effectiveness under the same nickel plating time. Therefore, compared with the composite paper with only nickel plating, the synergistic effect of the nickel layer and the copper-plated BF gives the composite paper a more efficient conductive network and excellent electromagnetic shielding performance.

[0148] Test methods and conditions:

[0149] The scattering parameters (S11 and S21) in the frequency range of 8.2–12.4 GHz (X-band) were obtained by the waveguide method using a Rohde & Schwarz ZNB20 vector network analyzer, and the electromagnetic shielding performance of the composite paper was evaluated.

[0150] The power coefficients of reflection (R), transmission (T), and absorption (A), as well as the total EMI SE (SET), reflected SE (SER), and absorbed SE (SEA) are calculated as follows:

[0151] R=|S 11 |2 (1)

[0152] T=|S 21 | 2 (2)

[0153] 1=A+R+T (3)

[0154] SE T =SE A +SE R +SEM (4)

[0155] SE R =-10log|1-R| (5)

[0156] SE A = -10log|T / (1-R)| (6)

[0157] Where SEM represents the multiple reflection SE between the two surfaces of the paper. If SET ≥ 15 dB, SEM can be ignored. In addition, SE / t is used to express the ratio of shielding effectiveness to thickness, where thickness is expressed in mm.

[0158] The morphological characteristics of the composite paper were analyzed using a field-emission scanning electron microscope (SEM, TESCAN, 5 kV). The tensile strength was assessed using a tensile tester (AI-7000-NGD, Goodtechwell) at a speed of 5 mm / min. The electrothermal conversion performance of the composite paper was investigated using a DC power supply (MS-6050, MAISHANG) at a certain voltage, and the temperature of the composite paper was measured using an infrared thermal imager (FLIRi7).

[0159] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper, characterized in that: The steps include: S1, acid etching of basalt fiber using piranha solution; S2, modifying the basalt fiber after acid etching in S1 with an amino silane coupling agent; S3, placing the basalt fiber modified in S2 in an activation solution for activation treatment and cleaning, and then placing it in a reducing agent solution for reduction treatment and cleaning; S4, placing the basalt fiber obtained in S3 in a chemical plating solution for chemical copper plating to obtain a copper-plated basalt fiber mixed solution; S5, mixing the copper-coated basalt fiber mixture obtained in S4 with the aramid nanofiber dispersion, and preparing a composite paper by a vacuum-assisted filtration method; S6, activating and cleaning the composite paper prepared in S5, and then placing it in a reducing agent solution for reduction and cleaning; S7, placing the composite paper obtained in S6 in a chemical plating solution for chemical nickel plating; S8, drying the nickel-plated composite paper obtained in S7 to obtain a double conductive network electromagnetic shielding paper.

2. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The piranha solution in S1 is a mixture of sulfuric acid and hydrogen peroxide in a volume ratio of 1:1 to 3:1; the acid etching time is 0.5 to 2 hours, and the acid etching temperature is 70 to 100°C.

3. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The S2 is specifically as follows: first, an amino silane coupling agent is hydrolyzed with a mixed solution of ethanol and deionized water in a mass ratio of 1:1 to 10:1 to obtain an amino silane coupling agent solution with a concentration of 1 to 5 wt%, wherein the amino silane coupling agent includes at least one of KH550, KH792, and KH602; then, acid-etched basalt fiber is added for modification, wherein the concentration of the acid-etched basalt fiber is 0.5 to 6 g / L, the modification temperature is 40 to 80°C, and the modification time is 8 to 24 hours.

4. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The composition of the chemical copper plating solution in S4 is 10-60 g / LLEDTA-2Na, 10-50 g / LNaKC4H4O6, 5-25 g / LCuSO4·5H2O, 0.01-0.2 g / LK4Fe(CN)6, 10-60 ml / LCH2O, 0.01-0.5 g / L 10 H8N2, the plating temperature is 40-80°C, the pH value of the copper plating solution is 10-12, and the plating time is 20-80 min; the content of the copper-plated basalt fiber in the copper-plated basalt fiber mixed solution is 50-90wt%.

5. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The preparation process of the aramid nanofiber dispersion in S5 is specifically as follows: aramid fibers, potassium hydroxide, dimethyl sulfoxide and deionized water are mixed and stirred to crack the aramid fibers to form aramid nanofibers, and then deionized water is added to perform a protonation reduction reaction. After repeated washing, the aramid nanofiber dispersion is obtained.

6. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The activation solution in S3 and S6 is silver nitrate solution, and the reducing agent is sodium borohydride solution; The S3 and S6 are specifically as follows: immersing the modified basalt fiber in a silver nitrate solution with a concentration of 5 to 20 g / L for a reaction of 5 to 60 minutes, and then rinsing with deionized water; then immersing the modified basalt fiber in a sodium borohydride solution with a concentration of 20 to 50 g / L for a reaction of 10 to 30 minutes, and then rinsing with deionized water again.

7. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The nickel plating solution in S7 is composed of 10-40 g / L C6H5Na3O7·2H2O, 10-40 g / L NiSO4·6H2O, 5-20 g / LNaH2PO2·H2O, 1-5 g / L DMAB, and 0.01-0.1 g / L SDS. The plating temperature is 30-80°C, the pH value of the nickel plating solution is 9-12, and the plating time is 10-100 min.

8. The method for preparing a double conductive network structure basalt fiber electromagnetic shielding paper according to claim 1, characterized in that: The drying temperature in S8 is 80-120° C., and the drying time is 8-80 minutes.

9. A basalt fiber electromagnetic shielding paper with a double conductive network structure, obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The thickness of the double conductive network electromagnetic shielding paper is 0.02-0.2 mm; the total electromagnetic shielding effectiveness of the double conductive network electromagnetic shielding paper against a frequency of 8.2-12.4 GHz is 10-90 dB.

10. Application of the double conductive network structure basalt fiber electromagnetic shielding paper according to claim 9 in the fields of smart films, personal thermal management or wearable electromagnetic protection.

Citation Information

Patent Citations

  • Basalt fiber / aramid nanofiber composite paper with self-assembled layered structure and preparation method of basalt fiber / aramid nanofiber composite paper

    CN116240748A

  • Manufacturing method of continuous carbon fiber-reinforced composite materials and manufacturing method of composite formed article

    KR1020180020541A